2005
DOI: 10.1002/jhet.5570420101
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosteroids: Synthesis of purinyl-steroid derivatives under mitsunobu reaction conditions

Abstract: The feasibility of using the Mitsunobu reaction for coupling of purines with steroids to obtain nucleosteroids was investigated in the particular case of 6‐chloropurine and cholesterol. Three principal products were obtained: 3βbT‐(6‐chloropurin‐9‐yl)‐5‐cholestene (1), 3α‐(6‐chloropurin‐9‐yl)‐5‐cholestene (2), and 6βbT‐(6‐chloropurin‐9‐yl)‐3,5‐cyclocholestane (3), isolated with 10.5%, 22.7%, and 12.6% yield, respectively. The stereochemical and structural diversity of the coupling products are explained by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…e 1 H-NMR spectrum (Table 1) of 1 in deuterated chloroform showed two purine hydrogen signals at δ [13] and adenine [14], which suggests that 1 is a hybrid of the two molecules. Considering that the C(3) ketocarbonyl carbon signal of the steroid nucleus is replaced by a new methine signal (δ H 5.32 (br dd, J � 5.2, 4.8 Hz); δ C 48.9), we inferred that the hybrid molecule was connected between C(3) of the steroid nucleus and N(9′) of the adenine moiety [15,16], and this deduction was further confirmed by heteronuclear multiple bond correlation . e chemical shift of C(3) (δ C 48.9 ppm (d)) revealed that the adenine moiety is α-oriented (axial direction) [15].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…e 1 H-NMR spectrum (Table 1) of 1 in deuterated chloroform showed two purine hydrogen signals at δ [13] and adenine [14], which suggests that 1 is a hybrid of the two molecules. Considering that the C(3) ketocarbonyl carbon signal of the steroid nucleus is replaced by a new methine signal (δ H 5.32 (br dd, J � 5.2, 4.8 Hz); δ C 48.9), we inferred that the hybrid molecule was connected between C(3) of the steroid nucleus and N(9′) of the adenine moiety [15,16], and this deduction was further confirmed by heteronuclear multiple bond correlation . e chemical shift of C(3) (δ C 48.9 ppm (d)) revealed that the adenine moiety is α-oriented (axial direction) [15].…”
Section: Discussionmentioning
confidence: 95%
“…Considering that the C(3) ketocarbonyl carbon signal of the steroid nucleus is replaced by a new methine signal (δ H 5.32 (br dd, J � 5.2, 4.8 Hz); δ C 48.9), we inferred that the hybrid molecule was connected between C(3) of the steroid nucleus and N(9′) of the adenine moiety [15,16], and this deduction was further confirmed by heteronuclear multiple bond correlation . e chemical shift of C(3) (δ C 48.9 ppm (d)) revealed that the adenine moiety is α-oriented (axial direction) [15]. e stereochemistry of C(3) was further confirmed from the following nuclear Overhauser effect spectroscopy (NOESY) correlations (Figure 3): H(8′) ⟷ H(1α)/H(2α), H(1α) ⟷ H(9), and H(2β) ⟷ Me-18.…”
Section: Discussionmentioning
confidence: 95%
“…It is worth noting here that Mitsunobu reactions of cholesterol lead in some cases to mixtures of products, resulting from assistance from the ethylenic bond, 10 although examples of the selective C-3 substitution with inversion of the configuration are also known. 11 A cyclic voltammetry study of 3 in dichloromethane solution showed that this compound undergoes reversible one-electron oxidation at 254 mV (vs Fc + /Fc) with DE = $70 mV.…”
mentioning
confidence: 99%